Functional and Structural Outcomes After Arthroscopic Rotator Cuff Repair With or Without Preoperative Corticosteroid Injections. Issue 3 (March 2023) - Feng, Sijia; Li, Huizhu; Zhong, Yuting; Xie, Yuxue; Chen, Jun; Chen, Yuzhou; Chen, Shiyi
Background: Corticosteroid injections (CSIs) are effective in alleviating pain in patients with rotator cuff tears, but controversy still exists regarding their potential adverse effects on clinical outcomes after rotator cuff repair. Purpose: To compare both the functional and the structural outcomes in patients who underwent arthroscopic rotator cuff repair with or without preoperative CSIs. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective cohort study was carried out among patients who underwent arthroscopic rotator cuff repair for partial- and full-thickness tears between 2015 and 2019. The patients who received preoperative CSIs were included in the CSI group and compared with a group without preoperative CSIs (non-CSI group), matched at a ratio of 1:2 based on tear size, age, and follow-up time. Both functional evaluation and structural assessments using magnetic resonance imaging (MRI) were performed at the final follow-up. Clinical outcomes—including retear rate as the primary outcome; pain; functional scores including the Constant-Murley score, American Shoulder and Elbow Surgeons score, and Fudan University Shoulder Score; range of motion (ROM); tendon integrity; tendon healing type; and cartilage thickness—were compared between the 2 groups with a statistical significance of P < .05 and power of 0.9. Results: Thirty-one patients were included in the CSI group, and 62 were included in the non-CSI group. After a mean 3-year follow-up, the 2 groups demonstrated no significant differences in retear rate; visual analog scale for pain; shoulder functional scores; and active ROM including forward flexion, abduction, external rotation, and internal rotation. No significant differences were observed on postoperative MRI scans of the rotator cuff tendon (tendon integrity, healing type, residual tendon attachment area, etc), cartilage thickness, and muscle atrophy. Conclusion: No significant differences were found at a mean 3-year follow-up in the retear rates, pain, ROM, and glenohumeral structure on postoperative MRI scans after arthroscopic rotator cuff repair with or without preoperative CSIs.